Immunohistochemistry evaluation of BMP-2 with beta-tricalcium phosphate matrix, polylactic and polyglycolic acid gel, and calcium phosphate cement in rats - Silva de Oliveira, Julio Cesar da [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; Sonoda, Celso Koogi [UNESP]; Okamoto, Roberta [UNESP]; Garcia-Junior, Idelmo Rangel [UNESP] (Springer, 2017)
Purpose The installation of implants has become a routine procedure in the clinic. However, it takes time and adequate bone thickness, and for that, tissue engineering has made efforts to develop substitutes for autografts, in view of certain disadvantages of this material. The decision to choose the most suitable graft material for each case is an important step in the success of bone reconstruction. This study was to verify, by means of immunohistochemical study, that the addition of bone morphogenetic protein had some influence on biomaterials commercially available, taking into account the formation of mineralized tissue, bone replacement, and the amount of degradation of biomaterials. Methods The sample consisted of 72 rats that were divided into eight treatment groups, in which two defects of 5 mm were made in each animal calvaria. Euthanasia was performed at 5, 15, and 30 days postop. Results A histologic and histometric analysis was performed to quantitate the area of mineralized tissue formed, the area of newly formed bone, and the area of degradation of the biomaterials. Data were analyzed with multiple comparisons of means by Tukey contrasts, and significant difference was assigned at the level of P < 0.05. The proteins used for immunohistochemical analysis accounted for the process of formation, mineralization, and bone resorption and was performed using ordinal qualitative analysis, where from assigning scores. Conclusions Bone morphogenetic protein 2 was shown to be effective as an inducer of bone formation process independent biomaterial used mainly for accelerating the resorption process of the framework.
Keywords: Bone regeneration; Tissue scaffolds; Dental implants; Rats